2016
DOI: 10.1159/000449099
|View full text |Cite
|
Sign up to set email alerts
|

Prenasal Thickness, Prefrontal Space Ratio and Other Facial Profile Markers in First-Trimester Fetuses with Aneuploidies, Cleft Palate, and Micrognathia

Abstract: Objective: To investigate the feasibility and reproducibility of the prenasal thickness (PNT)/nasal bone length (NBL) ratio, maxilla-nasion-mandible (MNM) angle, facial profile line, profile line distance, and prefrontal space ratio (PFSR) in the first trimester of pregnancy, develop normal ranges, and evaluate these markers in abnormal fetuses. Methods: All measurements were performed on stored images by two operators. Feasibility, interoperator agreement, and prediction intervals were calculated for all meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 20 publications
7
38
1
1
Order By: Relevance
“…Retrospective assessment of the images of anomalies missed by non-FMF-trained sonographers (3 spina bifida cases and of 4/5 facial clefts) showed that early markers of abnormal development, such as absent intracranial translucency [14] and abnormal maxilla-nasion-mandible angle, were clearly visible [15]. This suggests that further training in recognition of these markers might have increased detection of these cases.…”
Section: Discussionmentioning
confidence: 98%
“…Retrospective assessment of the images of anomalies missed by non-FMF-trained sonographers (3 spina bifida cases and of 4/5 facial clefts) showed that early markers of abnormal development, such as absent intracranial translucency [14] and abnormal maxilla-nasion-mandible angle, were clearly visible [15]. This suggests that further training in recognition of these markers might have increased detection of these cases.…”
Section: Discussionmentioning
confidence: 98%
“…Bakker et al berichteten, dass die pränasale Dicke bei etwa einem Drittel der aneuploiden Feten über der 97,5ten Perzentile liegt [50]. Die "prefrontal space ratio" aus dem zweiten Trimenon wurde etwas vereinfacht als "prefrontal space distance" untersucht [53].…”
Section: Auffälligkeiten Im Bereich Des Mittelgesichtsunclassified
“…The Fetal Medicine Foundation and associated research groups, often trained by the Fetal Medicine Foundation, have developed algorithms/markers used in daily clinical practice at 11–13 weeks to detect high-risk populations for an adverse pregnancy outcome such as fetal defects, chromosomal abnormalities, premature birth, and pre-eclampsia [4-10, 12, 13, 15-18]. Implementing those, we have learned that it is always better in a clinical setting to collect and combine all valid available information to reduce false positive rates and increase detection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our suggested combined approach to detect or exclude high-risk pregnancies for CLP would imply maxillary gap sign and measurement of PMD assessed in mid-/parasagittal views at the same time of nuchal translucency evaluation and coronal cross-sections as described by Sepulveda et al [13]. Other markers described by Bakker et al [18], such as the maxilla-nasion-mandible angle and 3D sonography as described by Martinez-Ten et al [19] using multiplanar cross-sections, could also be included using a combined approach. However, limitations we experienced using the maxilla-nasion-mandible angle as a marker are, firstly, the frontal portion of the maxilla which is often differently shaped and, secondly, implementing an angle with minute measurements.…”
Section: Discussionmentioning
confidence: 99%